The Effect of Tax Planning, Deferred Tax Expense, Deferred Tax Assets, Dividend Policy, Debt Policy on Profit Management in Infrastructure Sector Companies, as Well as Transportation and Logistics Listed on the IDX for the 2019-2023 Period - Made Meiliana Kurnia Sari; Juan Carlos Pangestu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine tax planning, deferred tax burden, deferred tax assets, dividend policy, and debt policy on earnings management in infrastructure, transportation, and logistics companies listed on the Indonesia Stock Exchange for the period 2019-2023. This study uses secondary data, namely data obtained indirectly, with the sampling technique in this study using the purposive sampling technique. The number of samples obtained was 84 observation data. The analysis method of this study uses descriptive quantitative analysis processed using SPSS version 29. The results of the study indicate that partial tax planning and deferred tax burden do not have a significant effect on earnings management, while deferred tax assets, debt policy, and dividend policy have a significant effect on earnings management. Simultaneously, tax planning, deferred tax burden, deferred tax assets, dividend policy, and debt policy have a significant effect on earnings management. It is hoped that this paper can be used as evaluation material on the impact of tax legislation that is still in the early stages of development in Indonesia, which has an impact on future business performance, and so that further research uses a wider research sample and other variables such as current tax burden, company size, and tax aggressiveness.